Light and electron microscopic features of tropical ulcer. Issue 10 (October 1987) - Adriaans, B; Hay, R; Lucas, S; Robinson, D C
Abstract : The histopathological features of 20 tropical ulcers with the electron microscopic findings on seven biopsy specimens are reported. The main findings were loss of epidermis associated with extensive dermal oedema, infiltration by polymorphonuclear leucocytes, and disruption of collagen bundles. The presence of micro-organisms at the site of tissue damage was shown and compared with the morphology of the organisms grown in culture. The most commonly identified bacteria were pleomorphic rods whose electron microscopic appearances accorded most closely with Fusobacteria grown in vitro. Spirochaetes, identified ultrastructurally as Treponema sp, were also present. There was no evidence of vasculitis to explain the rapid onset of ulceration, but necrotic changes seen in the dermis and the inflammatory cell infiltrate suggest that, associated with cell necrosis, bacteria previously shown in vitro have an important role in the pathogenesis of tropical ulcers.